The emergent role of artificial intelligence in Mathematics education: Examining students’ acceptance and perception - Yuli Bangun Nursanti; Imam Sujadi; Ira Kurniawati; Riki Andriatna; Arum Nur Wulandari (UIN Raden Mas Said Surakarta, 2025)
Artificial intelligence (AI) is increasingly being integrated into education, offering new opportunities for enhancing learning, especially in challenging subjects like mathematics. However, there is limited research on how students perceive and accept AI in mathematics education, particularly in the context of Indonesian higher education. This study aims to explore mathematics education students’ acceptance and perceptions of AI tools in enhancing their learning experience. Using a sequential explanatory mixed-methods design, the study employed a Technology Acceptance Model (TAM) questionnaire for quantitative data and in-depth semi-structured interviews to gather qualitative insights. The participants were 389 mathematic students from several universities in Surakarta municipality, Indonesia based on non-probability sampling technique through sampling quota. The results show that students generally perceive AI as useful and easy to use, with high scores for Perceived Usefulness (PU) and Perceived Ease of Use (PEU). AI was appreciated for its ability to provide personalized learning, immediate feedback, and flexibility. However, students' Behavioral Intention to Use (BIU) AI was lower, indicating hesitation toward integrating AI regularly into their learning routines. The findings highlight that while AI has the potential to enhance learning, students still value traditional face-to-face interactions with instructors and are concerned about over-reliance on technology. The study contributes to theoretical framework that AI tools should complement, not replace, traditional teaching methods. Practically, the integration of AI in education should be gradual, with adequate support for both students and instructors. Future research should explore long-term adoption and investigate the role of educational policies in supporting AI integration.